Use of trumpets techniques in "Sing Sing Sing " by Benny Goodman / Ahmad Zarul Hakim Mohd Nazaruddin - Mohd Nazaruddin, Ahmad Zarul Hakim (2022)
One cannot play a proper swing song without having the right technique and feel. "Sing Sing Sing". One of the famous swing songs in the big band era was originally composed by Louis Prima and later popularized by Benny Goodman. The character of the song that has a bright trumpet sound makes it a trademark in this song. This paper focuses on the trumpet technique used in the song "Sing Sing Sing". By using the qualitative method which involves collecting and analyzing, it is to identify the trumpet of the technique used. Through resources such as video performance and score analysis of trumpet techniques, I have made a comparison between several performances to identify the use of trumpet techniques from Benny Goodman with other performances. The paper gives an explanation of the techniques used as well as a comparison of the use of trumpet techniques used by other performances.